2015
DOI: 10.1016/j.ijgo.2015.06.031
|View full text |Cite
|
Sign up to set email alerts
|

Management options and fertility‐preserving therapy for premenopausal endometrial hyperplasia and early‐stage endometrial cancer

Abstract: Conservative management could be appropriate for carefully selected women with complex atypical endometrial hyperplasia or early-stage endometrial cancer who desire future fertility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 42 publications
1
28
0
3
Order By: Relevance
“…Conservative treatment strategies maintaining fertility have been described for both atypical hyperplasia and well-differentiated FIGO stage IA endometrial carcinoma without myometrial invasion. 25,26 Expert review was previously suggested for such patients to minimize risk associated with preserving the uterus. 27 Our findings clearly support such a recommendation and concur with published treatment guidelines for endometrial carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Conservative treatment strategies maintaining fertility have been described for both atypical hyperplasia and well-differentiated FIGO stage IA endometrial carcinoma without myometrial invasion. 25,26 Expert review was previously suggested for such patients to minimize risk associated with preserving the uterus. 27 Our findings clearly support such a recommendation and concur with published treatment guidelines for endometrial carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Although initial reports were promising, GnRH only exhibited low response rates in cases with previous exposure to P4 (43). Also, the prolonged use of GnRH and aromatase inhibitors can lead to symptoms of menopause such as bone loss, osteoporosis, and endometrial atrophy (44). Based on its successful use in ovarian cancer, Poly (ADP-ribose) polymerase (PARP) inhibition recently also found its way into the treatment of EC.…”
Section: Discussionmentioning
confidence: 99%
“…(Zivanovic et al ,2009; Bogani et al ., 2015). Currently, fertility preservation options in endometrial cancer are limited to hormonal methods (Signorelli et al ., 2009; Gressel et al ., 2015). Patients desiring to proceed with conservative hormonal management should be extensively counseled regarding potential risks as no scientifically proven optimal progestin regimen exists (Eskander et al ., 2011; Loren et al ., 2013; von Wolff et al , 2015).…”
Section: Introductionmentioning
confidence: 99%
“…It is important to emphasize that such an approach is not standard and should be considered only if the patient insists (Bogani et al ., 2016; Gressel et al ., 2015). Careful and thorough counseling is mandatory in this setting (Loren et al ., 2013; Lambertini et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation